AB0177 ARE THERE ANY CLINICAL AND SEROLOGICAL DIFFERENCES BETWEEN PATIENTS WITH PRIMARY AND SECONDARY (SLE) ANTIPHOSPHOLIPID SYNDROME?. (June 2019) - Dryglewska, Magdalena; Majdan, Andrzej; Majdan, Maria
Abstract : Background: Antiphospholipid syndrome (APS) could be diagnosed as primary (PAPS) or secondary (SAPS - accompanying other diseases, mainly found in patients with systemic lupus erythematosus -SLE) Objectives: The aim of our study was to determine if pts with PAPS and SAPS had different clinical and serological status. Methods: The study involved 80 (59-f and 21-m) APS patients (pts) 24 pts had PAPS and 56 pts had APS following SLE. In the whole study group the mean age was: 39.3± 12.7 years (range 18-71), the duration of the disease was 8.8 ± 8.3 years (range 0-37). The presence of aPL was detected in patients' serum using the commercially available tests: aPL-immunodot assay Anti-Phospholipid 10 Dot, for the qualitative detection of IgG or IgM antibodies. The statistical data analysis was performed using Statistica v13.0 Results: In the study group of 80 patients we have detected the presence of the following aPLs: a- cardiolipin IgM -37%, IgG -50.6%; a-phosphatidic acid IgM -19.7%, IgG -13.3%; a-phosphatidylcholine IgM and IgG -1.2; a-phosphatidylethanolamine IgM -1.2% and IgG -0; a-phosphatidylglycerol IgM – 5.0%, IgG -12.5%; a-phosphatidylinositol IgM-10.0%, IgG-12.5%; a-phosphatidylserine IgM-31.0%, IgG-50.6%; a-annexin V IgM -20%, IgG -10%; a-β2-GP I IgM-44.5%, IgG-35.0%; a-prothrombin IgM -44.5%, IgG-30%. The following clinical symptoms of APS were also present: stroke -10%, arterial/venous thrombosis -34%, pulmonary embolism-16.3%, obstetric complications-25.4%, nephropathy – 30.0%, hypertension-43.8%, valve defects 15.0%, livedo reticularis 11.2%, convulsions/chorea-6.2%, thrombocytopenia- 23.7% of the study group. During the study we detected statistically significant differences in the frequency of occurrence of aPLs between groups with PAPS and SAPS: a-phosphatidylinositol p=0, 0345; a-β2-GP I IgM p=0.004; a-prothrombin IgM p=0.0108 a-phosphatidic acid IgM p=0.045 (table 1 ) There are no differences in the assessed clinical symptoms between pts with PAPS and SAPS, apart from significantly higher frequency of the deep vein thrombosis in pts with PAPS (p- 0.04). Conclusion: The clinical pictures of PAPS and SAPS are similar. Only deep vein thrombosis occurs more frequently in pts with PAPS. Some classic and novel aPLs occur more frequently in pts with PAPS than in SAPS, and maybe could become a biomarker of PAPS Disclosure of Interests: Magdalena Dryglewska: None declared, Andrzej Majdan: None declared, Maria Majdan Speakers bureau: MSD, UCB, Abbvie, Roche